Population Differences and Host Species Predict Variation in the Diversity of Host-Associated Microbes in Hydra - Taubenheim, Jan; Miklós, Máté; Tökölyi, Jácint; Fraune, Sebastian (Frontiers in Microbiology, 2022)
Most animals co-exist with diverse host-associated microbial organisms that often form complex communities varying between individuals, habitats, species and higher taxonomic levels. Factors driving variation in the diversity of host-associated microbes are complex and still poorly understood. Here, we describe the bacterial composition of field-collected Hydra, a freshwater cnidarian that forms stable associations with microbial species in the laboratory and displays complex interactions with components of the microbiota. We sampled Hydra polyps from 21 Central European water bodies and identified bacterial taxa through 16S rRNA sequencing. We asked whether diversity and taxonomic composition of host-associated bacteria depends on sampling location, habitat type, host species or host reproductive mode (sexual vs. asexual). Bacterial diversity was most strongly explained by sampling location, suggesting that the source environment plays an important role in the assembly of bacterial communities associated with Hydra polyps. We also found significant differences between host species in their bacterial composition that partly mirrored variations observed in lab strains. Furthermore, we detected a minor effect of host reproductive mode on bacterial diversity. Overall, our results suggest that extrinsic (habitat identity) factors predict the diversity of host-associated bacterial communities more strongly than intrinsic (species identity) factors, however only a combination of both factors determines microbiota composition in Hydra.